In vitro antidiabetic and antimicrobial activity of Dracocephalum heterophyllum Benth. essential oil from different sites of North-western Himalayas India. Issue 6 (19th March 2023) - Chander, Ram; Maurya, Antim K.; Kumar, Kushal; Kumari, Sareeka; Kumar, Rakshak; Agnihotri, Vijai K.
Abstract: Dracocephalum heterophyllum Benth (Lamiaceae) is a wild herb that possesses a number of biologically active phytomolecules. The aim of this study was to investigate comparative essential oils (EOs) composition and biological (antimicrobial and anti-diabetic) activities of D. heterophyllum from higher altitudes. Gas chromatography-mass spectrometry (GC/MS) and gas chromatography-flame ionisation detector (GC-FID) were carried out for the identification and quantification of EOs components. The hydrodistillation of fresh aerial part of D. heterophyllum gave (0.1–0.8) % w/v EOs yield. Altogether, twenty-seven constituents were identified in the among samples representing (91.0–98.2) % of the EOs composition. The β -citronellol (31.5–83.7) % contributes major constituent in all samples. The in vitro antimicrobial potential of EOs was examined against six human pathogenic bacterial and two phytopathogens fungal strains. Anti-diabetic activity exhibits excellent α -amylase and better α -glucosidase enzymes inhibitor properties. Graphical Abstract: UF0001